PEMBUATAN TRAINING KIT SISTEM FUEL INJECTION SUZUKI LETâS FI - , DWI SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automotive industry have been created and made by purposed to fulfil transportation requirement for them. Automotive industry has developed very reped growth, this is shown with a lot of vurlover vehide in Indonesia. Every automotive product needs maintenance and repairing. The study is amed student can understand about gasoline injection system through trainer kit simulation of Suzuki Letâs FI injection system. Writer makes this study with using collection data method through literature and collection data through design and observation, observation through interview and directly observation. At injection system trainer all component can be used very well based on testing was done with determine terd methode from testing and observation for components, there for writer make conclude that gasoline injection system trainer can be very well suitable with each function it, start from main component until support components like sensor.